Pendampingan Wirausaha Mikro Pengrajin Rumahan Untuk Produk Olahan Eceng Gondok Bernilai Ekspor - Rustam, Suhardi; Lomagio, Afriana; Fadli, Muh; Patilima, Vina Saputri; Paramata, Faldimas (Jurnal Pengabdian kepada Masyarakat UBJ, 2025)
Program Pendampingan Masyarakat Pemula (PMP) aimed at developing water hyacinth crafts in Alata Village, Gorontalo. This home craft industry has great potential to improve the local economy and environmental sustainability. The assistance explained the importance of lake water hyacinth weed as a raw material for environmentally friendly crafts, as well as the challenges faced by craftsmen in production, management and marketing. The resulting crafts, such as bags and furniture, have export prospects, but require further support in terms of skills, resources and promotion.The proposed solutions include partnerships with raw material suppliers, technical training, increasing production efficiency, as well as marketing and financial management training. This program also emphasizes digital marketing, with the aim of expanding the market reach of artisans and building export channels. The methodology used includes training sessions, provision of equipment and consistent monitoring to ensure project sustainability. This initiative is in line with Indonesia's Green Economy goals, encouraging environmentally friendly business practices while empowering local craftsmen. Through this program, students will also gain direct experience in business management including creating digital products from the environment, integrating their learning with community service.